Crime and punishment perspectives from the humanities - Sarat, Austin (Amsterdam ; Boston : Elsevier JAI, 2005)
Volume 37 of "Studies in Law, Politics, and Society" presents a special issue devoted to exploring humanistic perspectives on the subject of punishment. Drawing together a distinguished group of interdisciplinary scholars, it explores the way "deviant" subjects are constructed and made available for punishment, the philosophical context within which decisions about punishment are made, and the inner workings of the penal apparatus. Diverse in their theoretical inspirations and approaches, the articles published here represent a significant advance in our understanding of the complex intersections of punishment, politics, and culture.
Includes bibliographical references.
Description based on print version record.
Keywords: Punishment -- Philosophy; Criminal law -- Philosophy; Criminals -- Public opinion; Imprisonment -- Social aspects; Imprisonment -- Moral and ethical aspects; Criminals -- Rehabilitation; Jurisprudence & philosophy of law; Social Science -- Sociology -- General; Law -- Criminal Law -- General